Genome-Wide Analysis of the DUF4228 Family in Soybean and Functional Identification of GmDUF4228–70 in Response to Drought and Salt Stresses - Leng, Zhi-Xin; Liu, Ying; Chen, Zhan-Yu; Guo, Jun; Chen, Jun; Zhou, Yong-Bin; Chen, Ming; Ma, You-Zhi; Xu, Zhao-Shi; Cui, Xi-Yan (Frontiers in Plant Science, 2021)
Domain of unknown function 4228 (DUF4228) proteins are a class of proteins widely found in plants, and play an important role in the response to abiotic stresses. However, there have been few studies on the DUF4228 family in soybean (Glycine max L.). In this study, we identified 81 DUF4228 genes in the soybean genome and named them systematically based on chromosome distribution. These genes are unevenly distributed on the 20 chromosomes of soybean. The predicted soybean DUF4228 proteins were divided into four subgroups (Group Ⅰ to Ⅳ) based on a phylogenetic tree. Genetic structure analysis showed that most of the GmDUF4228 genes have no introns. Expression profiling showed that GmDUF4228 genes are widely expressed in different organs and tissues. RNA sequencing data were used to study the expression profiles of GmDUF4228s under drought and salt treatments, and the expression levels of nine genes were further determined by quantitative real-time PCR (qRT-PCR). GmDUF4228-70 was selected for further functional analysis because it was found to be upregulated under drought and salt stresses in both RNA-seq and qRT-PCR analysis. Under drought stress, the degree of leaf curling and wilting of the GmDUF4228-70-overexpressing (GmDUF4228-70-OE) line was lower than that of the empty vector (EV) line. GmDUF4228-70-OE lines also showed higher proline content, relative water content (RWC), and chlorophyll content, and lower malondialdehyde (MDA), H2O2, and O2- contents. Under salt stress, the changes in phenotypic and physiological indicators of transgenic plants were the same as those under drought stress. In addition, overexpression of the GmDUF4228-70 gene promoted the expression of marker genes under both drought and salt stresses. Taken together, the results indicate that GmDUF4228 genes play an important role in the response to abiotic stresses.